Mild thermal treatment-driven transformation of CuOx assisted with the rearrangement of Al sites in Cu-SSZ-13 - Dongxu Han; Ying Xin; Junxiu Jia; Jin Wang; Zhaoliang Zhang (Applied Catalysis O: Open)
The Cu-SSZ-13 catalyst has been commercialized for the selective catalytic reduction (SCR) of NOx with NH3 in diesel exhaust purification, due to its superior activity, stability and environmental friendliness in comparison with traditional V2O5-WO3/TiO2 catalysts. Unfortunately, the currently prevalent preparation methods for Cu-SSZ-13 catalysts still present the challenge of uneven dispersion of the Cu species, which restricts the accessibility and utilization of the active ingredients, thereby resulting in unsatisfactory SCR performance. Herein, a straightforward and effective mild thermal treatment approach was proposed to obtain highly dispersed Cu2+ active sites, which endows the Cu-SSZ-13 catalyst with enhanced activity. X-ray absorption fine structure (XAFS), in situ Raman, in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS), electron paramagnetic resonance (EPR), and nuclear magnetic resonance (NMR) characterizations demonstrated that the Cu species in the aggregated CuOx clusters underwent redispersion and transformation into Cu2+ ions, which were trapped by the rearranged Al sites of zeolites during the mild thermal treatment process. This provided a viable solution for the improvement of SCR performance of Cu-SSZ-13 catalysts at industrial scale-up.